Environmental Olympism”: perspectives in sports, Olympic education and culture - Grassi, David (Πανεπιστήμιο Πελοποννήσου, 2021)
To become a pillar of the Olympic movement, environmentalism should be explicitly stated in the Fundamental Principles of Olympism. It is not just a matter of recognizing the central role of the planet earth as the home of humanity based on the core values of excellence, respect and friendship. Environmental protection should be guaranteed through changes in the practice of sport, Olympic education, and culture, which can be derived directly from the definition of Olympism.
Keywords: Olympism; Olympic movement; Olympic education; Environmental protection; Environmental policy; Environmental education; Ολυμπισμός; Ολυμπιακό κίνημα; Ολυμπιακή παιδεία; Περιβαλλοντική προστασία; Περιβαλλοντική πολιτική; Περιβαλλοντική εκπαίδευση; Olympism; Environment; Sustainability; Sport